THE EFFECT OF USING GEMINI AI-BASED LEARNING MEDIA ON STUDENTS' MATHEMATICAL CONCEPT UNDERSTANDING ABILITY - Widyaningrum, Ismi; Fadliansyah, M.; Mustakim, Usep Saepul (Cakrawala Pedagogik, 2025)
This research aims to determine the effectiveness of using Gemini AI-based learning media on the ability to understand mathematical concepts in class XI TKJ SMK Al-Kaffah Cikedal students in the 2024/2025 academic year. The design used in this research was to provide a pre-test after which treatment using Gemini AI learning media was applied to the experimental class with a total of 26 people, and ordinary treatment (learning using conventional models) to the control class with a total of 25 students, after the treatment was carried out. then a post-test was used to measure the results of students' ability to understand mathematical concepts from each group. Based on the results of research and data analysis, the average post-test score for the experimental class was 75.5 and the control class was 61.9. This shows that there are significant differences in the learning outcomes obtained by the two classes. From the results of the hypothesis test calculations, tcount = 7.617. At a significance level of 5% and db = 26+25 – 2 = 49, ttable = 2.010. Because tcount > ttable (7.617 > 2.010) then H0 is rejected which means H1 is accepted, which means there is a positive influence of the Gemini AI learning media on the ability to understand mathematical concepts of class.